Experimental and theoretical investigation of the fluid behavior during polymeric fiber formation with and without pressure - ÇAM, MUHAMMET EMİN (AMER INST PHYSICS, 2019)
The fabrication of polymeric micro/nanofibers is gaining attention due to their use in an array of applications including tissue engineering scaffolds, nanosensors, and fiber-reinforced composites. Despite their versatile nature, polymeric fibers are widely underutilized due to the lack of reliable, large-scale production techniques. Upon the discovery of centrifugal spinning and, recently, pressurized gyration techniques, new research directions have emerged. Here, we report a comprehensive study detailing the optimal conditions to significantly improve the morphology, homogeneity, and yield of fibers of varying diameters. A series of polymeric fibers was created using a 21 wt.% solution of polyethylene oxide in distilled water and the fluid behavior was monitored inside a transparent reservoir using a high-speed camera. Fabrication of the fibers took less than 1 s. Using centrifugal spinning, we studied the formation of the fibers at three different rotational speeds, and for pressurized gyration, one rotational speed was studied with three different nitrogen gas pressures. Using the pressurized gyration technique at a gas pressure of 0.3 MPa, there was significant improvement in the production yield of the fibers. We found a strong correlation between the variation of pressure and the rate of the solution leaving the reservoir with the improved morphology of the fibers. The use of reduced power techniques, like centrifugal spinning and pressured gyration, to yield high-quality nonwoven nanofibers and microfibers in large quantities is important due to their use in rapidly expanding markets. (C) 2019 Author(s).
Keywords: ELECTROSPUN NANOFIBERS